The cubic polynomial f(x) is defined by f(x) = 2x^3 -7x^2 + 2x + 3. Given that (x-3) is a factor of f(x), express f(x) in factorised form.

f(x) = (x-3)(2x^2 - x - 1)f(x) = (x-3)(2x +1)(x-1)x = 3, -1/2, 1 are roots of the cubic equation.

Answered by Oliver M. Maths tutor

7862 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve the simultaneous equations, 2x+y-5=0 and x^2-y^2=3


In this question, take 'log' to mean 'log base 5'. Solve the equation log(x^2-5)-log(x) = 2*log(2)


Differentiate expressions of form Ax^b where A and b are constants and x is a variable


Find the equation of the tangent to the curve y = 2 ln(2e - x) at the point on the curve where x = e.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences